2022
DOI: 10.1136/heartjnl-2022-321610
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine-associated heart failure: a systematic review of observational studies

Abstract: ObjectiveTo conduct a systematic review of observational studies on methamphetamine-associated heart failure (MethHF) .MethodsSix databases were searched for original publications on the topic. Title/abstract and included full-text publications were reviewed in duplicate. Data extraction and critical appraisal for risk of bias were performed in duplicate.ResultsTwenty-one studies are included in the final analysis. Results could not be combined because of heterogeneity in study design, population, comparator, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
(191 reference statements)
0
5
0
Order By: Relevance
“…Meth cessation is a cornerstone of optimal patient care. Existing studies provide moderate-strength evidence that meth cessation is associated with reversal of cardiac dysfunction, left ventricular remodeling, and improvement in NYHA functional class ( 100 ). Reduced exposure to the sympathomimetic effects of meth likely results in better blood pressure control.…”
Section: Diagnostic Challenges and Managementmentioning
confidence: 99%
“…Meth cessation is a cornerstone of optimal patient care. Existing studies provide moderate-strength evidence that meth cessation is associated with reversal of cardiac dysfunction, left ventricular remodeling, and improvement in NYHA functional class ( 100 ). Reduced exposure to the sympathomimetic effects of meth likely results in better blood pressure control.…”
Section: Diagnostic Challenges and Managementmentioning
confidence: 99%
“…Heart failure associated with methamphetamine use (MethHF) is increasingly prevalent and associated with significant morbidity. In a systemic review of 21 studies addressing MethHF, Manja and colleagues5 found that recovery of left ventricular function after abstinence can be predicted by echocardiography and the extent of fibrosis. Guideline directed medical therapy and female sex are associated with better outcomes (figure 3).…”
mentioning
confidence: 99%
“…Furthermore, the dose needed to harm is unknown. Is a single use enough to trigger a cascade leading to heart failure or must an individual use daily for years?’ He concludes that ‘The work of Manja et al 5 highlights that the standard of care academically and clinically must be a broad team across the care spectrum to simultaneously address methamphetamine use, heart failure and social determinants of health.’…”
mentioning
confidence: 99%
“…In this issue of Heart , Manja et al report on an important and necessary systematic review of the current published literature, seeking to address some of these issues. Their review included 21 studies: 14 retrospective cohort studies, three case-control studies, two studies with a prospective cohort and two administrative data studies 8. They found that MethHF was associated with increased severity of heart failure and more readmissions.…”
mentioning
confidence: 99%
“…Understanding this heterogeneity is critical because, as Manja et al have shown, it is very difficult to study something without a clear consensus on a definition 8. As highlighted in table 4, there is so much more to classifying a patient’s relationship with methamphetamine than simply a positive urine drug screening (UDS).…”
mentioning
confidence: 99%